(untitled) (Medical Forum Monthly, 2024)
Objective: Objective of study was assessment of fibrinogen and albumin levels association with orthopedics traumatic patients’ outcome who received massive transfusion Study Design: Observational / cross sectional study. Place and Duration of Study: This study was carried out at orthopedic department of a tertiary care Hospital, Peshawar from March 2014 to July 2015 Materials and Methods: In all patients, the initial resuscitation was performed as soon as admitted to the emergency room. Blood samples were obtained at admission and after 24 h. Part of the serum was frozen and stored at -70°C for determination of fibrinogen and albumin by an immunoturbidometric assay. Electrolytes, hemoglobin, and hematocrit levels were measured on admission. For early restoration, normal saline or ringer was used, clinical events were recorded thereafter until death or hospital discharge. Result: We were studied forty six traumatic patients with severe limb injuries and result showed that 20 patient (41.3%) and 27 (58.7%) were alive. There was significant difference outcome observed in fibrinogen level after 24 h and in case of albumin levels, there was no significant difference observed. Conclusions: When orthopedics traumatic patients received massive transfusion, fibrinogen level play significant role in determination of these patients, while serum albumin is not important factor.